Profil fitokimia dan aktivitas antioksidan dari minyak atsiri kulit buah Jeruk Pontianak (Citrus nobilis lour. var. Microcarpa): Profil fitokimia dan aktivitas antioksidan dari minyak atsiri C.nobilis - Farianti Wiranda; Ika Rahayu; agus Limanto (Jurnal MedScientiae, 2023)
Abstract. Citrus nobilis lour fruit. var. microcarpa (C. nobilis) or Pontianak Orange is a food source with good vitamins and antioxidants, while the peel was considered as waste. Along with technological development, people processed it by utilizing its essential oil. Research showed that the essential oil of Pontianak orange peel (C. nobilis) could inhibit the growth of some gram-positive and -negative bacteria. Still, the compounds' composition and antioxidant and anti-inflammatory properties have not been studied much. Therefore, this study aimed to determine the active compound composition, antioxidant, and anti-inflammatory activity of C. nobilis essential oil. The essential oil from C. nobilis peel was extracted using the clavenger method. The GCMS methods was used for active compound profiling. The antioxidant activity of essential oils was examined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical. The dominant active compound components in C. nobilis essential oil were limonene, β-myrcene, and linalool. The essential oil of C. nobilis had robust antioxidant activity (IC50 13.114 µg/mL) compared to BHT. The content of the dominant active compound in the essential oil supported this activity.